Astigmatoma - Naser, Maryam; Hooshi, Parizad; Mortazavi, Martin; Westfal, Danielle; Schultheis, Wayne; Hashemi, Nafiseh (Journal of Ophthalmology and Research, 2021)
Difficulty with reading may come from refractive errors including astigmatism, but also can arise from neurological disease causing difficulty focusing. We present a patient referred to neuro-ophthalmology clinic after initial treatment of astigmatism by Lasik was failed to address the patient’s main complaint.